Supplementation of Dietary Nano Zn-Phytogenic on Performance, Antioxidant Activity, and Population of Intestinal Pathogenic Bacteria in Broiler Chickens - C. Hidayat; Sumiati Sumiati; A. Jayanegara; E. Wina (Faculty of Animal Science, Bogor Agricultural University, 2021)
Zinc is one of the essential minerals that are important for poultry. The disadvantage of Zn in the conventional form is its low bioavailability. One of the efforts to increase the bioavailability of Zn is to make it in a nano form. Nano Zn-Phytogenic (NZP), is a combination of Zn and phytogenic compounds of plants in nanoparticle size. The NZP was self-produced utilizing the green synthesis process of inorganic Zn and guava leave extract (Psidium guajava). The objective of this study was to evaluate the effects of supplementation NZP in diet on the performance, antioxidant status, and population of pathogenic intestinal bacteria (Escherichia coli and Salmonella sp) of broilers chicken. This study used 180 males and 180 females of Lohman broilers day old chick (DOC). The experiment was subjected to a completely randomized design with 6 (six) treatments and 5 (five) replications, and each experimental unit consisted of 12 DOCs (6 males and 6 females). The treatment given in this study were; R1= basal diet; R2= R1 + Zn Sulfate (90 mg Zn/kg) + 5.32 mg/kg guava leaf flour with 12.82% water content (added as a source of phytogenic compounds); R3= R1 + NZP (45 mg Zn/kg); R4= R1 + NZP (90 mg Zn/kg); R5= R1 + NZP (135 mg Zn/kg); R6= R1 + NZP (180 mg Zn/kg). The variables observed were performance, antioxidant activity in meat, and population of pathogenic intestinal bacteria (E. coli and Salmonella sp) of broiler chicken. The results showed that the addition of NZP up to a dose of 90 mg Zn/kg in the diet improved (p<0.05) body weight gain compared to the basal diet. The addition of NZP had no significant effect on the FCR. The addition of NZP increased (p<0.05) SOD activity in meat when compared with the dietary treatment without NZP. Groups of chicken fed NZP (R3, R4, R5, R6) had significantly (p<0.05) lower E. coli and Salmonella sp population. It could be concluded that the addition of NZP up to a dose of 90 mg Zn/kg in the diet of broiler chicken had positive benefits in improving performance, increasing antioxidant activity, and reducing pathogenic intestinal bacteria (E. coli and Salmonella sp).